Description and characterization of leaf anatomy of Asian Palmyra Palm – Borassus flabellifer L. - Esakkimuthu,; Ravichandran,; Manimekalai, (The Bioscan, 2026)
Anatomical investigation of Asian Palmyra palm Borassus flabellifer L. was carried out, with the following objectives, description and characterization of vascular, fibro vascular bundles and fibrous sheaths from leaf. Comparative anatomical studies were done between lower, middle and upper regions of leaf pinnae with reference to diversity of fibro vascular bundles and other tissues. Free hand section of Palmyra leaf lamina was taken for anatomical and histochemical studies. Leaf lamina segments were macerated using Jeffery’s fluid to study leaf fibres. Staining was done using histochemical stains such as Safranin ‘O’, Toluidine blue- ‘O’, Sudan III, Oil red, Nile blue, and fluorochromes such as Acridine orange & Rhodamine. Leaf peelings were taken for stomatal studies and micrometric measurements. Parameters such as length & width of all cells, and wall thickness were made and the results were statistically analyzed. Leaf epidermis is covered by a thick waxy cuticle layer. Hypodermis is made of very thick wall cells.